IMPLEMENTASI MEDIA PERMAINAN TAPAK GUNUNG UNTUK MENGEMBANGKAN KEMAMPUAN HOTS TERHADAP LITERASI BAHASA - Virna Alfina Dewi; Annur Nanda Arsy; Yasfi Muyasaroh; Putri Rahayu S (Fakultas Tarbiyah dan Keguruan, 2025)
The development of science and technology in the era of globalization provides new challenges for basic education, especially in fostering students' critical thinking skills through innovative learning media. One of the efforts that can be made is to integrate traditional games as learning media. This study aims to develop learning media based on the Tapak Gunung game and test its feasibility, practicality, and effectiveness in improving literacy skills and analytical abilities of elementary school students. The type of research used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were fifth grade students of SDN Marga Mulya, Tangerang Regency. Data were obtained through observation, questionnaires, expert validation, and small and large scale trials. The results showed that the Tapak Gunung learning media met the valid criteria with the percentage of media, language, and material expert assessments above 80%. In addition, student responses in small and large group trials reached 80-86% with practical and effective categories. The implementation of the media also increased student engagement, strengthened understanding of the S-P-O-K sentence pattern, and stimulated critical thinking skills through fun literacy activities. This study concludes that literacy-based Tread Mountain learning media can be an innovative alternative in the learning process.